Writing groups in the writing center: negotiating authority and expertise in collaborative learning - Wilder, Sara, author; Utah State University Press, publisher (Colorado State University. Libraries, 2025)
Through 3 group case studies, Wilder uses qualitative methods to analyze how students learn together to write in new genres and for new audiences, theorizing the processes by which writing groups negotiate authority and expertise in academic writing by centering group writing.--Provided by publisher.
Keywords: Writing centers; Writers' workshops; Authorship -- Study and teaching (Higher) -- Evaluation; College students' writings -- Evaluation; Academic writing -- Study and teaching (Higher)